Reassessment of known fossil Pyraloidea (Lepidoptera) with descriptions of the oldest fossil pyraloid and a crambid larva in Baltic amber - Heikkilä, Maria; Simonsen, Thomas J.; Solis, M. Alma (Zootaxa, 2018)
The identifications of known fossils currently placed in the lepidopteran superfamily Pyraloidea are critically re-examined. Of the eleven fossils examined, only three are confirmed to show morphological characters supporting placement in the superfamily. These fossils include a crambid larva in Baltic Amber, Baltianania yantarnia, Solis gen. n. et sp. n. and the oldest known fossil pyraloid, Eopyralis morsae Simonsen, gen. n. et sp. n. The third fossil, Glendotricha olgae Kusnezov, 1941, displays apomorphic characters for Pyraloidea, but is shown to be an inclusion in copal, not Baltic amber as had been reported. Seven fossil specimens lack reliable characters and cannot be assigned to Pyraloidea with certainty: Pyralites obscurus Heer, 1856; Pyralites preecei Jarzembowski, 1980; Petisca dryellina Martins-Neto, 1998; three fossil larvae tentatively identified as Pyralidae by Zeuner (1931); and Gallerites keleri Kernbach, 1967. A possible fossil pyraloid in Mizunami amber could not be located in museum collections and available literature does not provide details to assess the validity of the identification. We discuss the contribution of the reliably identified fossils towards better understanding the evolutionary history of Pyraloidea.